Structural transformation, export promotion policy options, and their impact on the Indian economy: A social accounting matrix (SAM) approach - P Venkatesh; Barun D Pal; Sarvesh K Dubey; V Sangeetha; Balasubramanian M; Renjini V R; D R Singh; Amit Kar; Balaji S J; Suresh Pal (Agricultural Economics Research Review, 2023)
The export promotion policy of the processed and unprocessed foods sectors affects output growth in the farm and non-farm sectors; labour and capital intensity; the shift in labour demand across gender and education; and the inequality in income distribution in rural and urban households. This study uses the social accounting matrix (SAM) multiplier model to examine the impact of the export promotion policy in India. The economy has undergone structural transformation, but the income inequality index has not improved. Based on structure of the economy in 2007-08 (SAM) promotion of unprocessed foods-based export policies would be more powerful in accelerating output growth, whereas, processed foods-based policies will be more influential in 2012–13 (SAM).